POTENTIAL OF CURATELLA AMARICANA L. AGAINST SARS-COV2: BIOAVAILABILITY, MOLECULAR SIMILARITY AND MOLECULAR DOCKING BETWEEN SECONDARY METABOLITES AND PROTEASE TYPE 3-CHYMOTRYPSIN (3CLPRO) - Emildo Marcano; Ysbelia Sánchez (Journal of the Chilean Chemical Society, 2021)
We report the bioavailability analysis for six secondary metabolites with antiviral, antioxidant and antitumor activity reported, from Curatella amaricana L. Additionally, the molecular similarity analysis of each metabolite is presented and compared with Lopinavir, Ritonavir, Darunavir, Cobicistat and Nelfinavir, which actually are in the third phase for the production of a new vaccine for SARS-Cov2. The mode of interaction through molecular docking between each structure and the zone of action for protease type 3-chymotrypsin (3CLpro) also is presented. The molecular geometry for structures were optimized at semiempirical PM6 level. The bioavailability and molecular docking calculations were performed using the algorithms incorporated in chemoinformatic servers and AutoDock Vina. The results show that the structures studied lead a moderated permeability through the cell membrane, by complying with Lipinski's "rule of 5”. Molecular similarity was evaluated by averaging geometric parameters (3D-Shape) and electrostatic potential (ESP). The results show that the most secondary metabolites would have a similar mode of action as the Lopinavir, with average similarity between 0.65 and 0.73. This last idea is reinforced by the results for molecular docking with the 3CLpro active site, highlighting the interaction of the molecules studied with the amino acid residues: His-41, Phe-140, Gly-143, Ser-144, Cys-145, His-163, Glu-166 and His-172, with an range interaction-free energy between -7.2 kcal/mol and -9.2 Kcal/mol, highlighting Quercetin 3-O-Alpha-L-rhamnoside with improve affinity energy than Lopinavir.